EVALUATION OF FINANCING HUMAN CAPITAL OF REGIONS UNDER DIGITALIZATION - I. Ershova; O. Belyaeva; A. Obukhova (Вестник Северо-Кавказского федерального университета)
In article the main trends in the dynamics and structure of financing education in the leading Western countries are considered in the framework of the concept of cost sharing. The ratio of private and public spending on education, student spending on tuition, the main forms of state support for students and their families are analyzed. The analysis of the demandfor private educational loans to students and households. The authors compare the dynamics of financing and the number of students, which makes it possible to identify positive and negative trends in the development of higher education. The analysis shows that in the period under review, the differentiation of higher education systems into two groups increased, with increasing and decreasing state funding. The analysis showed that the system offinancing higher education in developed countries is signiicantly diferent. Today, investment in education is seen as the most important factor in improving competitiveness, leading to the continuous growth of the economy.